Standard Versus Tubeless Percutaneous Nephrolithotomy in Children: A Comparative Study at Tertiary Care Centre - Sayed Ghafar Shah, Muhammad Kamran Khan, Ali Asad, Naqib Ullah, M Asif Khan, Naveed Ahmad Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Percutaneous nephrolithotomy is a urological technique advocated to extract kidney and proximal ureter calculi. Various strategies evolved throughout time as a result of experiences and new instruments. Tubeless PCNL is chosen over traditional PCNL due to fewer post-operative problems, a shorter patient hospital stay, and shorter procedure duration. This is the first of its kind study, to our knowledge in paediatric population in our setup. Objective: To compare the outcomes of standard versus tubeless percutaneous nephrolithotomy in children. Material and Methods: This prospective descriptive comparative study conducted at Department of Paediatric Urology, Institute of Kidney Disease, Peshawar; from October 2021 to September 2022 consisting of 100 patients. Patients in the age range of 4 to 14 years with renal or ureteric stones were arbitrarily assigned to two groups. Group A underwent through standard PCNL and group B underwent through tubeless PCNL. Outcomes of both groups were compared in terms of operative time, post-op pain and post-op complications. All the data was analyzed through SPSS version 24. Results: Mean age of the patients in group A and B was 9.12±2.07 years and 8.68±1.82 years respectively. The mean operation time, hospital stay in group A (standard PCNL) and B (tubeless PCNL) were 86.06 ±7.20 minutes, 6.46±.97 days and 83.68 ±3.81 minutes and 3.42±.81days respectively. The mean VAS pain scores in group A and group B were 6.24 ± .71 and 3.70 ± .81 respectively. Post operative complications were less seen in the tubeless PCNL. Conclusions: Tubeless PCNL is a safe technique having shorter operative time while post-operatively associated with shorter hospital stay and fewer complications as compared to standard PCNL. Keywords: Renal Stones, Standard PCNL, Tubeless PCNL, Outcomes Abbreviations: PCNL=Percutaneous Nephrolithotomy, VAS=Visual Analogue Scale